2020
DOI: 10.3390/su13010084
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap for Innovators in the Process of Innovation for Development

Abstract: This study aims to provide valuable insights into the process of innovation for development. We selected the “Reinvent the Toilet Challenge”, an initiative of the Gates Foundation, with the objective of creating sustainable sanitation solutions for the 2.5 billion people across the globe who lack access to safe and affordable sanitation. The Naturally Acceptable and Technologically Sustainable (NATS) team at the Asian Institute of Technology (AIT), Thailand was appointed by the Gates Foundation to serve as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Research on social capital for respondents in Poland and Lithuania confirmed the findings of Hadjielias et al [28], specifically that a high level of social capital, especially trust, facilitates the entrepreneurial process. Moreover, the authors agree with Koottatep et al [35], in that, by analyzing (and understanding) the interactions of company innovators with stakeholders, i.e., key partners, we can better understand the innovation process for development. This will allow us to develop responsible research and innovation (RRI) methods, i.e., research that will not only help a business make profits, but also contribute to the common good of society and science.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Research on social capital for respondents in Poland and Lithuania confirmed the findings of Hadjielias et al [28], specifically that a high level of social capital, especially trust, facilitates the entrepreneurial process. Moreover, the authors agree with Koottatep et al [35], in that, by analyzing (and understanding) the interactions of company innovators with stakeholders, i.e., key partners, we can better understand the innovation process for development. This will allow us to develop responsible research and innovation (RRI) methods, i.e., research that will not only help a business make profits, but also contribute to the common good of society and science.…”
Section: Discussionsupporting
confidence: 68%
“…This is needed because companies are often unaware of the negative consequences of inappropriate innovation implementation [34]. To prevent the negative effects of irresponsible innovation, the European Commission introduced a framework for responsible research and innovation (RRI) [35]. In this framework, implementing RRI requires multiple stakeholders to work together to find solutions to societal challenges.…”
Section: Conceptual Problems In Implementing Rri In Science and Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…The trend towards an increasing complexity comes from the fact that since 1970, complex technologies comprising the 30 most valuable world goods exports increased from 43% to 84% (Kash and Rycroft, 2002). Moreover, because of several scientific disciplines and knowledge areas that need to be integrated and multiple players needed to be involved, the complexity of innovation processes keeps growing (Koottatep et al, 2021). As a result, the innovation journey tends to progress in unpredictable ways over time in a nonlinear cycle of divergent and convergent activities (Van De Ven, 2017).…”
Section: Complex Product and Systems (Cops) In Contemporary Industrymentioning
confidence: 99%
“…Referring to EU innovation policies, Clark and Guy (1998) identify in the EU a number of paradoxes in the relationship between research and productivity, due to the inability of many Member States to make the most of their existing innovation base; the two authors consider the linear models of innovation to be outdated and propose "focusing European policies on promoting the diffusion and efficient use of technologies in order to close the development gaps and solve the paradoxes of research and productivity" (Clark and Guy, 1998, p. 389). Along the same lines, Shim and Shin (2022) show that the value of R&D investment does not necessarily have an impact on the performance of R&D programs, so that in order to generate the efficient effects of innovation it is necessary to add an efficient management of the innovative process (Tidd and Bessant, 2018), to use a highly qualified human resource (Koottatep, Sukavejworakit and Virasa, 2021) and to adopt adequate marketing strategies and implementation of R&D programs (Chabowski and Mena, 2017).…”
Section: Review Of the Scientific Literaturementioning
confidence: 99%